Upaya Pengelolaan Pasien Diabetes Mellitus Tipe 2 Dengan Underweight Dalam Pendekatan Kedokteran Keluarga - Yolanda Restiani; Noviana Zara (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
The patient came with complaints that the body often felt weak even though the patient did not do strenuous activities. This complaint has worsened in the last 1 week, causing the patient to be discouraged from doing activities and disrupting his daily activities Patient also complained that his weight was decreasing. Another complaint that was felt was that the hands often felt numb. History of diabetes mellitus in the last 10 years, but the patient admitted that he did not routinely take medicine to control his blood sugar. The KGDS examination obtained in the patient was 324 mg/dl. The patient's BMI was 18.2 kg/m2 and classified as underweight. Primary data was obtained through autoanamnesa and physical examination by conducting home visits, filling out family folders, and filling out patient files. Assessment was carried out based on holistic diagnosis at the beginning, process, and end of the visit quantitatively and qualitatively. Interventions include education about the causes of diabetes mellitus, education about lifestyle modification and the importance of taking medication regularly to control blood sugar levels and explaining complications that may arise from the patient's disease so that patients make preventive efforts.